Laser-Particle Collider for Multi-GeV Photon Production - Magnusson, J; Gonoskov, A; Marklund, M; Esirkepov, T Zh; Koga, J K; Kondo, K; Kando, M; Bulanov, S V; Korn, G; Bulanov, S S (Physical review letters, 2019)
As an alternative to Compton backscattering and bremsstrahlung, the process of colliding high-energy electron beams with strong laser fields can more efficiently provide both a cleaner and brighter source of photons in the multi-GeV range for fundamental studies in nuclear and quark-gluon physics. In order to favor the emission of high-energy quanta and minimize their decay into electron-positron pairs, the fields must not only be sufficiently strong, but also well localized. We here examine these aspects and develop the concept of a laser-particle collider tailored for high-energy photon generation. We show that the use of multiple colliding laser pulses with 0.4 PW of total power is capable of converting more than 18% of multi-GeV electrons passing through the high-field region into photons, each of which carries more than half of the electron initial energy.